2013
DOI: 10.1016/j.ejvs.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The Shortfall in Long-term Survival of Patients with Repaired Thoracic or Abdominal Aortic Aneurysms: Retrospective Case–Control Analysis of Hospital Episode Statistics

Abstract: Long-term survival remains poor after aneurysm repair and adverse cardiovascular events are common relative to the wider population. Further research is required to characterise and optimise cardiovascular risk prevention in patients with aortic aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 28 publications
2
37
0
7
Order By: Relevance
“…Aneurysms typically grow by 2 mm per year and once the size exceeds 55 mm there is an increased risk of rupture, when patients are considered for open (OAR) or endovascular repair (EVAR) [4,5]. In the majority, mortality is not due to aneurysm rupture but relates to vascular ischemic events [6][7][8][9][10] irrespective of known cardiovascular disease (CVD) [11]. We and others have previously demonstrated that AAA patients exhibit a hypercoagulable state, with elevated circulating levels of thrombin activation markers and fibrin degradation products [12][13][14], which persist following aortic intervention [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Aneurysms typically grow by 2 mm per year and once the size exceeds 55 mm there is an increased risk of rupture, when patients are considered for open (OAR) or endovascular repair (EVAR) [4,5]. In the majority, mortality is not due to aneurysm rupture but relates to vascular ischemic events [6][7][8][9][10] irrespective of known cardiovascular disease (CVD) [11]. We and others have previously demonstrated that AAA patients exhibit a hypercoagulable state, with elevated circulating levels of thrombin activation markers and fibrin degradation products [12][13][14], which persist following aortic intervention [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…No clear evidence exists to suggest that overall survival among patients with AAA is greater in Sweden, or that Swedish cohorts are fitter and better candidates for surgery. Long‐term analyses of elective AAA repair in Swedish patients showed a crude mortality rate of 69 per cent at 5 years, whereas comparable English data suggest that elective AAA repair in England is associated with a 67 per cent 5‐year survival rate. In the present study, endovascular outcomes could not be adjusted for aortic morphology, particularly AAA size.…”
Section: Discussionmentioning
confidence: 53%
“…Patients with AAA have a substantial burden of baseline CVD and associated risk factors, and a reduced life expectancy compared with that in the general population. The present study demonstrates that this risk may be modifiable through the use of therapeutic interventions known to reduce CVD risk. This study highlights the importance of the cardiovascular risk associated with AAA, and the need for greater attention to risk management.…”
Section: Discussionmentioning
confidence: 70%
“…These findings explain the observation that patients with an AAA have twice the rate (1·4 versus 2·8 per cent per year) of adverse cardiovascular events (including death from CVD, non‐fatal myocardial infarction and non‐fatal stroke) compared with patients without an AAA. Patients with an AAA should receive evidence‐based treatments that reduce CVD risk, analogous to the secondary prevention of coronary heart disease (CHD).…”
Section: Introductionmentioning
confidence: 85%